PENGARUH MOTIVASI DAN POLA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. ANTAMA KHARISMA ROSARI - Rudi Bratamanggala dan Amin (Fakultas Ekonomi Universitas Borobudur, 2016)
Efforts to improve the quality of these human resources, especially human resources need to be done well, directed, and planned, so that the company can compete fairly with other companies, given the future competition between companies will be intense. HR can be able to compete with competitors or business partners are companies that have qualified human resources. The research objective was to determine the effect of motivation and leadership, the performance of employees of PT. KharismaAntama Rosary. This study used survey method by using primary data obtained from questionnaires. The samples in this study were 67 employees. Samples were taken by accidental sampling technique that is saturated sampling technique when all members of the population used as sampell ,. Data were analyzed using Path Analysis. The results showed that the correlation coefficient obtained is positive, reflecting the fact that motivation and leadership have a positive relationship with the performance, so the higher the leadership and motivation, the higher the performance of employees. From the results obtained is also known coefficient of determination that reflects how much the contribution of independent variables (motivation and leadership) on the dependent variable (performance), ie 0.948 or 94.8%, which means motivation and leadership patterns affect the performance of the remaining 94.8% by 5.2% influenced by other factors not examined. 1. There is the influence of motivation and leadership patterns affect the performance of employees of PT. KharismaAntama Rosary simultaneously. 2. There is a motivational effect on the performance of employees of PT. KharismaAntama partially Rosary. 3. There is a pattern of leadership influence on the performance of employees of PT. KharismaAntama partially Rosary. Keywords: motivation, leadership style, employee performance